PKM EDUKASI BERKALA PENGUNAAN SOFTSKILL TRAINING STRUCTURAL EQUATION MODELLING (SEM) - Kuncara, Tommy; Rahmat Jaya; Alamsyah; Abdul Muchlis; Sandy Suryady; Barizki, Rezzi nanda (Asosiasi Dosen Muda Indonesia, 2023)
This Community Service aims to provide assistance in Deepening Structural Equation Modeling (SEM) Features to Produce Quality Scientific Publications with the Association of Indonesian Young Lecturers (ADMI). This community service activity is a form of cooperation between Gunadarma University and the Association of Indonesian Young Lecturers (ADMI). This community service activity was carried out during the COVID 19 pandemic, so most of it was carried out through online and offline meetings. The target output for this semester's community service is focused on increasing the application of science and technology in the community on the basis of communicative Structural Equation Modeling (SEM) in-depth training and adding a simulation of Multiple Inier Regression. The result we hope is to be able to help fellow human beings and to ease the burden of life for the community in terms of statistical needs in the fields of Information Systems, Psychology, Computer Engineering, Accounting which are used for work and daily life as a new tourist destination in the city of Bekasi.